Otimização topológica dos nós fixos para algoritmos de trilateração baseados em RSSI - Bueno, Rafael de Souza (Universidade Federal de São Carlos, 2024)
The extensive use of locating devices in today's world is increasingly being used indoors. Depending on the structure of the environment in which you want to operate, there are many barriers that prevent these locators from working properly. To solve this problem, new technologies are being developed, mainly taking into account location based on the strength of the signal received, due to its ease of structuring and low cost. Position estimation methods involve trilateration algorithms. In this work, we proposed an optimization of the topology of the fixed nodes using the Received Signal Strength Indicator (RSSI) method, with the aim of analyzing the smallest error comparing the real and the estimated position in situations varying the arrangement of the fixed nodes in a given area of interest. It was analyzed which method obtained the greatest precision in its measurements. MATLAB software was used in conjunction with the genetic algorithm for simulations and the generation of heat maps for each different method, and then, with the results of these simulations, the average error and the average standard deviation were calculated in order to compare the results of the methods. The analysis of these results made it possible to determine the ideal situation of the bases where the topology is more precise. Satisfactory results were obtained from the simulations in relation to increasing the precision of the points found, after optimization with the delimiter R = 2.5m an average improvement in results was obtained between the three methods used in this work of 1,44% and with 2*R, an improvement of 20,65%.
Topological optimization of fixed nodes for RSSI-based trilateration algorithms
Keywords: Estimativa de posição; Received Signal Strength Indicator; Topologia; Trilateração; ENGENHARIAS::ENGENHARIA MECANICA